WILLIAM R. ROFF (1967), THE ORIGINS OF MALAY NATIONALISM, KUALA LUMPUR: UNIVERSITY OF MALAYA PRESS. 297 PAGES. - Mohamad Kamil, Ibrahim Majdi Bin (Journal of Al-Tamaddun, 2020)
This book review attempts to describe and analyze the concepts of Islamic schools of thought dedicated to the traditional group and reformer group as discussed by William R. Roff through the conception of ‘Kaum Tua’ and ‘Kaum Muda’ that is included as one of the chapter of his PhD thesis entitled ‘The Origins of Malay Nationalism’ which later was published as a book up to several editions. William R. Roff books and thesis has become one of the main references for the local and foreign researchers in discussing the aspect of Malay intellectuals of Malay people in Malaysia. This study uses a qualitative method. This study uses library research as the method of data collection, largely depends on primary sources and some secondary sources. In the data analysis methodology, generally, this study utilises the methods of historical and critical analysis respectively to analyze data on William Roff’s views on the evolution of Islamic schools of thought mainly through the group of ‘Kaum Tua’ and ‘Kaum Muda’. Furthermore, the methodology of content analysis is generally used in almost on collected data. Findings of this study conclude that the theory of William R. Roff on the Islamic thought remains relevant until today. William Roff’s concepts of ‘Kaum Muda’ and ‘Kaum Tua’ is still relevant to the present world and is an authoritative study to serve as reference material in discussing the development trends of Islamic thought in Malaysia.